Biocatalytic Synthesis of Pikromycin, Methymycin, Neomethymycin, Novamethymycin, and Ketomethymycin - Hansen, Douglas A. (2013)
A biocatalytic platform that employs the final two monomodular type I polyketide synthases (PKS) of the pikromycin pathway in vitro followed by direct appendage of D-desosamine and final C-H oxidation(s) in vivo was developed and applied toward the synthesis of a suite of 12-and 14-membered ring macrolide natural products. This methodology delivered both compound classes in thirteen steps (longest linear sequence) from commercially available (R)-Roche ester in >10% overall yields.